Pemberian Vitamin B Kompleks terhadap Pertumbuhan Ayam Maron BSM-1 di Desa Parparean II, Kecamatan Porsea, Kabupaten Toba - Diki Fransiskus Simarmata; Artomo Manalu; Jala Singkop Harianja; Silvester Sitorus; Yakub Nahum Marbun; Parsaoran Silalahi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This activity aims to encourage the growth of Maron BSM-1 Chicken before and after being given Vitamin B Complex. This activity was conducted by a team of student servants from HKBP Nommensen University Medan in Parparean II Village, Porsea District, Toba Regency. The methods used in this service activity include observation and experimentation. Based on the results of experiments in the field, the injection of Vitamin B Complex into Maron BSM-1 Chicken was carried out in 1 injection. The changes that occured within 1 week were that the appetite of the chicken livestock increased, the fat contained in the chicken livestock increased by about 3 ounces in 1 week and the health of he chicken livestock was better maintained. Thus, this method has proven effective in helping the community to increase the growth of Maron BSM-1 Chicken livestock and produce quality chicken meat. Through this research, the community can gain new knowledge in carrying out animal husbandry and this research can also be useful for other researchers as a reference carrying out community service.